On certain sequences of Fourier-Young coefficients of a function of Wiener's class - Siddiqi, Rafat (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
In this paper we study the summability of certain sequences of a function of WienerÂ´s class by N í¶rland method. From which we deduce under what conditions a function of WienerÂ´s class is continuous.